The complete mitochondrial genome of the basidiomycetous fungus, tinctoporellus epimiltinus strain RS1 - Ranjita Subramaniam; Vijay Subbiah Kumar; Shafiquzzaman Siddiquee (National Library of Medicine, 2024)
Tinctoporellus epimiltinus is widely known as a wood-decaying fungus. In the present study, we identi-fied the complete mitochondrial genome of this species using next-generation sequencing technology.Our findings revealed that the genomic structure is a circular molecule with a size of 51,878 bp.Consistent with most Basidiomycota species, it consists of 14 core protein-coding genes, one ribosomalprotein gene (rps3), 26 transfer RNA genes, and small and large ribosomal RNA (rns and rnl) genes.Seven additional open reading frames were identified. These included two sequences similar to DNApolymerases, an endonuclease-like sequence, and four hypothetical proteins. The mitochondrial gen-ome exhibited a nucleotide composition of A (36.24%), C (12.04%), G (13.18%), and T (38.55%), result-ing in a 25.21% GC content. A phylogenetic tree constructed using the combined mitochondrial genedataset provided insight into the phylogenetic relationships of this species within the context ofBasidiomycota and its members.